THE ROLE OF FAMILY CEREMONIES IN THE FORMATION OF MORAL AND AESTHETIC VALUES (Scientific journal of the Fergana State University, 2024)
This article deals with the formation of moral and aesthetic values through spiritual education in the family. The focus is on the nature of family rituals and traditions, and the process of developing new approaches to family rituals that reflect national values is analysed. The article highlights the significance of these values in the minds and everyday life of the people, as well as their influence on the formation of public consciousness and culture.